Verpackungsentsorgung in Deutschland - Alternative wirtschaftspolitische Instrumente im Vergleich. - Eich, Claudia (My University, 2007)
Die Arbeit untersucht den Markt für Verpackungsentsorgung in Deutschland. Dabei werden insbesondere im Bereich der Verkaufsverpackungen Ineffizienzen vermutet, weil es in dem Markt lange Zeit nur ein Unternehmen gab, das bundesweit die Erfassung von haushaltsnah anfallendem Verpackungsabfall organisiert hat - die Duales System Deutschland GmbH (DSD). Zwar haben sich seit 1998 Selbstentsorger-Lösungen und seit 2003 zwei alternative duale Systeme in einzelnen Bundesländern etabliert. Es stellt sich die Frage, ob der Markt für Verpackungsentsorgung in Deutschland nicht einer grundlegenden Reform bedarf. Deshalb ist das Ziel der Untersuchung eine Analyse des Verpackungsabfallmarktes, insbesondere hinsichtlich der Effizienz- und der Wettbewerbssituation, sowie das Aufzeigen von Reformoptionen für die Verpackungsentsorgung in Deutschland. Wegen der verordnungsbedingten Schwierigkeiten und des eingeschränkten Wettbewerbs wird untersucht, ob der Verpackungsentsorgungsmarkt mit anderen wirtschaftspolitischen Instrumenten als den in der derzeitigen Verpackungsverordnung vorgesehenen Rücknahmepflichten effizienter gestaltet werden könnte. Bei der Übertragung von verschiedenen Instrumenten auf den Markt der Verpackungsentsorgung hat sich gezeigt, dass die Kosteneffizienz stets besser ist als bei der gegenwärtigen Verpackungsverordnung. Da Selbstverpflichtungen die Gefahr von wettbewerbshemmenden Absprachen bergen und mit Beseitigungsabgaben ein treffsicheres Erfüllen der Verwertungsquoten nicht gewährleistet werden kann, wird im Fall einer grundlegenden Modifikation der Verpackungsverordnung die nähere Untersuchung von Verpackungszertifikaten empfohlen.

The present thesis analyses the packaging disposal market in Germany, starting from the assumption of inefficiencies, particularly with regard to sales packaging, since, for a long time being, only one company has organised the nationwide collection of packaging waste arising at private households namely Duales System Deutschland GmbH (DSD). In fact, self-management waste disposal solutions (since 1998) and two alternative Dual systems (since 2003) were established in single federal states. DSD however, whose supervisory board has decided during a meeting on October 11, 2004 to open up to the equity market, held a monopoly. This thesis represents the situation of May 2005. In June 2006, further companies received a pronouncement to be set up as a Dual system operator on a full-coverage basis. The German Packaging Ordinance shall be amended for the fifth time in 2007 in order to ensure the collection of sales packaging arising at private households. However, the question arises with regard to this current development whether the packaging disposal market in Germany requires a fundamental reform. The target of this study has therefore been an analysis of the waste packaging market, in particular with regard to the efficiency and competitive situation, as well as showing reform alternatives concerning packaging disposal in Germany. The German packaging disposal market is characterised by the Packaging Ordinance, including various recycling specifications for transport and outer packaging, for sales packaging arising in commercial and industrial sectors as well as at private households. Since this kind of differentiation proved to be difficult in practice, it is to be proposed to deregulate both the classification of self-management waste disposal solutions and Dual systems and of transport and sales packaging. In addition and due to the monopolistic position of DSD, the competitive situation within the waste disposal market for sales packaging has turned out to be problematic. In 2001, two decisions of the European Commission as to the trademark contract with manufacturers and distributors and as to the service contract with waste disposal companies have rendered possible competition of Dual systems. By accordingly interpretating the Packaging Ordinance, participants of self-management waste disposal solutions may however be disadvantaged with regard to the take-back point. By reason of difficulties due to regulations and of restricted competition, this thesis analyses whether the disposal market for packaging waste may be designed in a more efficient way by using other economic-political instruments than the take-back obligations required by the current version of the Packaging Ordinance. Given instruments shall have to be compatible with both the European Packaging Ordinance and the German Closed Substance Cycle and Waste Management Act and shall have to be able to fulfil the economic-political recycling quotas. Furthermore, economic-political possibilities of interference shall have to comply with high efficiency standards, since, in fact, incentives to achieve certain targets within the value-added chain seep away, a natural monopoly however does not occur and external effects are of relatively minor importance, compared to other waste types. Transferring different instruments to the packaging disposal market has proven that the cost efficiency is always superior to the current version of the Packaging Ordinance. Given the fact that self-commitments involve the risk of restrictive agreements and that disposal fees cannot guarantee an unerring fulfilment of recycling quotas, a closer analysis of packaging certificates in case of a fundamental modification of the Packaging Ordinance is highly recommended.
Packaging disposal in Germany - Alternative economic-political instruments by comparison.
Keywords: Entsorgung; Abfallwirtschaft; Abfallrecht; Wettbewerb; Wirtschaftspolitik; Entsorgungsmarkt; Verpackungsabfall; Verpackungsverordnung; Duales System; Rücknahmepflicht; Effizienz; Zertifikat